Remoção de nitrogênio e fósforo num sistema de recirculação para criação de tilápia do Nilo (Oreochromis niloticus) - Maigua, Y. A.; Sánchez, I. A.; Matsumoto, T. [UNESP] (My University, 2014)
The main objective of this research was to evaluate the performance of a column vertical flow settler and a conventional horizontal flow settler associated to an aerobic three-phase fluidized bed reactor with circulation in a recirculating aquaculture system for Nile tilapia farming. The hydraulic detention times of the reactor, the horizontal flow settler and the column settler were 0.198, 2.94 and 0.55 h respectively. For final fish stocking densities of 33 kg/m3(system with column settler) and with 30 kg/m3(conventional settler) the average removal efficiencies of total ammonia nitrogen, total nitrogen and total phosphorus were 36.6%, 26.3%, 46.5% and 26.2%, 24.3%, 32.3%, respectively with significant differences for total ammonia nitrogen; the cumulative feed burden for the two systems were: 2.64 and 2.22 kg of feed/m3of freshwater per day. The two evaluated systems demonstrated to be feasible options to maintain the water quality in the recirculating systems. The system with column settler showed better results due to the lesser volume and area requirements, the higher levels of total ammonia nitrogen removal efficiency and assimilative capacity of feed per unit volume.
Nitrogen and phosphorus removal in a recirculating system for Nile tilapia (Oreochromis niloticus) culture
Keywords: Aquaculture; Fluidized bed; Sedimentation; Wastewater treatment